IMPLEMENTASI KEBIJAKAN UPAH MINIMUM KOTA DUMAI (STUDI KASUS PADA KOPERASI KARYAWAN MARITIM (KOKARMAR) PT. (PERSERO) PELABUHAN INDONESIA I CABANG DUMAI) - Ulya Dian Yufia; Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Wage payment is one important issues in employment relationship. To protect workers from arbitrary wage by the company, Dumai city government set the minimum dumai city wage is Rp 1.287.600.00/month for the year 2012 which be regulated through Riau Governor Regulation no. 54 of 2011.This study want to see how the implementation of the minimum wage in Dumai city particularly at cooperative maritime employess PT. Pelindo Dumai branch and what are the follow up government to a cooperative maritime employess PT. Pelindo Dumai branch that does not run the minimum wage.The study was conducted using a qualitative approach. Techniques used in collecting data in the qualitative research are interviews and documentation. The data that has been collected and then processed qualitatively.Based on the research, it can be concluded that the implementation the Minimum Wage policy of Dumai City in 2012 have not been implemented in the cooperative maritime employess PT. Pelindo Dumai branch. Cooperative maritime employess PT. Pelindo Dumai branch give wages to workers Cleaning Service of Rp. 850.000.00/month. While the factors which become obstacles in the implementation of Riau Governor Regulation No. 54 of 2011 is :a. Structural weaknessb. Lack of reporting companies in manpower and transmigration Dumaic. Lack of facilities and infrastrusture supervision activitiesd. Workers lack complaint.Keyword: Implementation, Policies, Controlling, Minimum City Wage.